2019
DOI: 10.1111/jre.12715
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐year prospective clinical and patient‐centered trial on subepithelial connective tissue graft with or without enamel matrix derivative in Class I‐II Miller recessions

Abstract: Background and Objective The study compared clinical and patient‐centered outcomes of subepithelial connective tissue graft (CTG) with and without enamel matrix derivative (EMD) in the treatment of Class I‐II Miller periodontal recession defects. Material and Methods This prospective clinical study evaluated 80 patients over a 3 years follow‐up in a private periodontal practice. A total of 144 maxillary and mandibular anterior teeth were divided into two groups: group 1 (CTG with EMD—80 teeth) and group 2 (CTG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The authors concluded that EMD did not influence immunological parameters related to wound healing following gingival recession surgery. On the other hand, our findings are remarkably similar to the results of a study by Mercado et al [ 25 ], where the use of EMD as an adjunct to SCTG in the treatment of classes I and II Miller recessions resulted in significantly reduced pain on the 2nd, 7th, and 14th day after the surgery. In a very recent article, Lee et al [ 28 ] reported no difference in the severity of early post-operative discomfort and wound-healing events between subjects who underwent periodontal surgery with and without EMD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The authors concluded that EMD did not influence immunological parameters related to wound healing following gingival recession surgery. On the other hand, our findings are remarkably similar to the results of a study by Mercado et al [ 25 ], where the use of EMD as an adjunct to SCTG in the treatment of classes I and II Miller recessions resulted in significantly reduced pain on the 2nd, 7th, and 14th day after the surgery. In a very recent article, Lee et al [ 28 ] reported no difference in the severity of early post-operative discomfort and wound-healing events between subjects who underwent periodontal surgery with and without EMD.…”
Section: Discussionsupporting
confidence: 92%
“…Apparently, the addition of EMD to SCTG in the MCAT technique did not seem to influence clinical outcomes. On the contrary, the additional use of EMD to SCTG in multiple recession coverage procedures with coronally advanced flap was associated with better root coverage and improved keratinized tissue [ 25 ]. Cheng et al [ 26 ] performed meta-analysis and concluded that higher PPD reduction tends to occur when EMD was used additionally to SCTG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous subsequent studies eventually supported this broad spectrum of biofunctionality of EMD(Miron et al 2016b, Grandin et al 2012, Bosshardt et al 2008. Indeed, the general pro-wound healing effects of EMD are reflected in its established clinical effectiveness in periodontal regeneration(Esposito et al 2009), root overage procedures(Mercado et al 2020a, Mercado et al 2020b and the management of peri-implantitis(Mercado et al 2018, Isehed et al 2018. Furthermore, a number of other human histological studies have confirmed the periodontal regenerative potential of EMD(Rasperini et al 2000, Roman et al 2013, Sculean et al 2000, Cochran et al 2003.…”
mentioning
confidence: 97%
“…For the root coverage techniques, EMD has been related to an effective root coverage, foreseeable and easy to perform with reduced patient morbidity [30,31]. In addition, EMD demonstrated positive results with regards to keratinized tissue width (KTW) and complete root coverage [32]. In contrast, few studies revealed no significant difference for the gingival recessions in the clinical results between EMD treated and non-EMD treated sites [33][34][35].…”
Section: Introductionmentioning
confidence: 99%